2020
DOI: 10.1111/trf.15703
|View full text |Cite
|
Sign up to set email alerts
|

Current state of whole blood transfusion for civilian trauma resuscitation

Abstract: BACKGROUND Whole blood (WB) is rapidly emerging as the treatment modality of choice for the initial resuscitation of civilian trauma patients across the United States. The reemergence of WB has been rapid and driven in part by recognition of the importance of early plasma transfusion in the resuscitation process. STUDY DESIGN AND METHODS The study was designed as a critical analysis of the available literature on WB transfusion in civilian trauma patients. Studies were included if they reported on transfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Initial protocols for cold-stored LTOWB were initiated to support the Norwegian Armed Forces with trauma resuscitation in international operations in 2013. This development seems to be consistent with the increasing implementation of cold-stored LTOWB in civilian systems in other countries [29, 30].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Initial protocols for cold-stored LTOWB were initiated to support the Norwegian Armed Forces with trauma resuscitation in international operations in 2013. This development seems to be consistent with the increasing implementation of cold-stored LTOWB in civilian systems in other countries [29, 30].…”
Section: Discussionsupporting
confidence: 78%
“…Data suggest that transfusion of uncrossmatched LTOWB for catastrophic hemorrhage in the hospital is safe and that there is no significant difference in survival rates between nongroup O patients receiving incompatible plasma and group O patients receiving compatible plasma [37-40]. The available literature supports the feasibility and safety of LTOWB used in the treatment of civilian patients, but the evidence regarding clinical outcomes, particularly with direct comparison to balanced-ratio transfusions with components, is limited [29, 41]. Hence, with respect to hard endpoints, there is not enough evidence to support or refute the clinical superiority of LTOWB compared to component therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood is increasingly considered to be a better product for resuscitation, which is now being widely used in civilian emergency centers and military operations [1,2]. It contains all the elements of blood in nearly physiologic ratios, and particularly suitable for the resuscitation of severe traumatic hemorrhage patients [3,4]. Packed whole blood can be stored for up to 35 days in CPDA-1 under a refrigerated condition [5].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have used different methodologies and varying doses of WB 10‐15 . A 2020 review of WB studies concluded that there is substantial evidence that WB is safe and feasible, but it has not been shown to be superior to component therapy in any large or randomized studies 16 . More recently, published studies have shown conflicting results.…”
mentioning
confidence: 99%
“…To date, most of the published studies on this topic have been observational and performed at a single center bringing the bias inherent with these types of study designs 16 . The obvious next step is randomized controlled trials that compare clinical outcomes in patients treated with WB compared with component therapy.…”
mentioning
confidence: 99%